Ambulatory Blood Pressure Monitoring in Patients With Chronic Kidney Disease and Resistant Hypertension - Shafi, Salman (J Clin Hypertens (Greenwich), 2012)
J Clin Hypertens (Greenwich). 2012; 14:611–617. © 2012 Wiley Periodicals, Inc. The role of ambulatory blood pressure (BP) monitoring (ABPM) has not been well‐studied in patients with chronic kidney disease and resistant hypertension. In a retrospective study of the outpatient chronic kidney disease population, 156 patients with chronic kidney disease and resistant hypertension who had 24‐hour ABPM and clinic BP measurements were identified. Resistant hypertension was defined as uncontrolled clinic BP while taking ≥3 medications including a diuretic or controlled BP while taking ≥4 medications. Within the study group, ambulatory BP <130/80 mm Hg was found in 35.9% of all patients. Only 6.4% had both ambulatory and clinic BP <130/80 mm Hg. Prevalence of white‐coat hypertension, masked hypertension, and sustained hypertension were 29.5%, 5.8%, and 58.3%, respectively. Compared with patients with sustained hypertension, more patients in the white‐coat hypertension group had low nocturnal average systolic BP (defined as nocturnal average systolic BP <100 mm Hg) (17.4% vs 0%) and low 24‐hour average diastolic BP (defined as 24‐hour average diastolic BP <60 mm Hg) (52.2% vs 22%, P<.01). ABPM provides more reliable assessment of BP in patients with chronic kidney disease and resistant hypertension.